(untitled) (Bangladesh Journal of Medical Science, 2022)
In a technology –driven society, it is very essential to have effective communication skills as medical graduate with patients and peer members. Assessments are vital in the process of teaching and learning. Assessing oral presentation skills is considered as assessing the behavioural skills in Millers’ prism of Clinical competence in Medical Education. In alignment with the Saudi Med competency Framework, the rubric was designed keeping the core competency at the centre like Communication & Collaboration and arranging the other auxiliary competencies around, then the parameters like dimensions were derived. An evaluation rubric for grading the presentations was designed to allow faculty evaluators to objectively score student performances in the dimensions of presentation like speech elocution, eye contact along with subject content. Rubrics create clarity for students and rubric dimensions represent various outcomes for students, giving them a realistic destination for their assignment. The students are informed about plagiarism malpractices and are instructed to maintain academic integrity. In response to the COVID-19 pandemic, the rubric scoring assessment for oral presentation was used for online assessment on Zoom webinar. This assessment tool along with online conferencing tools has provided a framework for integrated and interactive evaluation that can be used to facilitate the modification of traditional assessment methods. Bangladesh Journal of Medical Science Vol. 21 No. 03 July’22 Page: 521-528